Acute Basilar Artery Occlusion Presenting With Convulsive Movements: A Systematic Review - Zhang, Dan; Chen, Yigang; Hao, Yonggang; Hu, Xingyue; He, Xudong (Frontiers in Neurology, 2022)
Background and purpose—Convulsive seizures related to posterior circulation stroke are considered rare. However, some patients with acute basilar artery occlusion (BAO) can present with convulsive movements. Misdiagnosed as seizures may delay the reperfusion therapy for acute BAO. In this study, we have summarized the clinical features and possible mechanisms of BAO presenting with convulsive movements. Methods—We performed an Institutional Review Board-approved institutional database query from 2015 to 2020 and a literature search of the online database PubMed. Clinical data were collected and analyzed. Results—In total, 14 patients with acute BAO presented with convulsions. There were 10 men and 4 women, with a mean age of 53 (range, 23–77) years. All of these patients had different degrees of impaired consciousness (100.0%, 14/14). Convulsive movements were the initial symptoms in 78.6% (11/14) of patients. Further, 64.3% (9/14) of patients presented with paralysis or cranial nerve abnormalities, and 85.7% (12/14) of patients were treated with reperfusion therapy (thrombolysis, 35.7% [5/14]; endovascular thrombectomy, 64.3% [9/14]). The BAO etiology and mechanism were related to embolism, vessel dissections, and severe stenosis of the right vertebral artery in 57.1% (8/14), 21.4% (3/14) and 7.1% (1/14) of patients, respectively; they were undefined in 14.3% (2/14) of patients. Moreover, 42.9% (6/14) of patients had a 90-day modified Rankin Scale score of 0–2, and the mortality rate was 21.4% (3/14). Conclusions—Acute BAO, especially that related to embolism or vessel dissection, may present with convulsive movements. Acute BAO is a devastating, but treatable disease if diagnosed in time. Considering the possibility of BAO is important when dealing with patients presenting with acute-onset convulsive movements. Prompt diagnosis and reperfusion therapy may help achieve a better prognosis.